Control of bromate ion and brominated organic compounds formation during ozone/hydrogen peroxide treatment of secondary effluent - Kim, H S (Water science and technology : a journal of the International Association on Water Pollution Research, 2006)
Ozonation and ozone process combined with hydrogen peroxide have been identified as new technologies for direct or indirect reuse of wastewater. This study aims to establish appropriate conditions to control the formation of BrO3 and brominated organic compounds during O3/H2O2 treatment of secondary effluents of sewage. When the H2O2/O3 mole ratio of injection was above 0.5 and the DO3 concentration was below 0.1 mg/L, BrO3 was controlled as well as treatment purpose was completed. TOBr formation in O3/H2O2 treatment was also completely controlled